Multiple Tendon Ruptures of Unknown Etiology. Issue 5 (October 2013) - Axibal, Derek P.; Anderson, John G.
Tendon ruptures are common findings in foot and ankle practice. The etiology of tendon ruptures tends to be multifactorial—usually due to a combination of trauma, effects of systemic diseases, adverse effects of medications, and obesity. We present an unusual case of right Achilles tendinitis, left Achilles tendon rupture, bilateral peroneus longus tendon rupture, and left peroneus brevis tendon rupture of unknown etiology. This case report highlights the need for research for other possible, lesser known etiologies of tendon pathology. Level of Evidence: Therapeutic, Level IV, Case Study